2020
DOI: 10.1186/s12859-020-3524-8
|View full text |Cite
|
Sign up to set email alerts
|

Computational identification of biomarker genes for lung cancer considering treatment and non-treatment studies

Abstract: Background Lung cancer is the number one cancer killer in the world with more than 142,670 deaths estimated in the United States alone in the year 2019. Consequently, there is an overreaching need to identify the key biomarkers for lung cancer. The aim of this study is to computationally identify biomarker genes for lung cancer that can aid in its diagnosis and treatment. The gene expression profiles of two different types of studies, namely non-treatment and treatment, are considered for disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
(80 reference statements)
0
3
1
Order By: Relevance
“…For instance, gene CTNND2 is located on Chr5, for which we demonstrated a greater eccDNA count per chromosome after length normalization in cancer samples (Figures 5C). Our assessments did not uncover any of the previously reported established biomarkers of lung cancer in our plasma eccDNA populations (5,29,30,(46)(47)(48)(49)(50).…”
Section: Discussioncontrasting
confidence: 51%
“…For instance, gene CTNND2 is located on Chr5, for which we demonstrated a greater eccDNA count per chromosome after length normalization in cancer samples (Figures 5C). Our assessments did not uncover any of the previously reported established biomarkers of lung cancer in our plasma eccDNA populations (5,29,30,(46)(47)(48)(49)(50).…”
Section: Discussioncontrasting
confidence: 51%
“…To the best of our knowledge, this is the first study that comprehensively evaluates all 12 topological network scoring metrics and their effectiveness in identifying cancer-related biomarkers in biological networks. Compared to previous studies that solely relied on popular metrics like Degree 15 17 , selected metrics without any validation or reasoning provided, or simply used all 12 metrics together 6 , 25 , which was shown to be inefficient in this study, our study thoroughly evaluates all 12 metrics using our proposed Integrated AUC. Moreover, many previous studies only used one metric or lacked effective metric composition, which is not enough to accurately quantify and characterize the disease network.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that genes do not function in isolation, and instead work together. As such, network-based approaches have emerged as powerful tools for investigating gene interactions and understanding their complex relationships 6 . In the past few years, topological data analysis (TDA) has revolutionized the oncology field, becoming one of the most powerful and widespread tools to extract useful information from high-dimensional biomedical data 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This includes gene expression, protein expression, and protein activity, the modulation of desired cellular phenotypes. 28 The protein/gene-protein/gene interaction networking, hub gene identification, gene enrichment, and functional gene annotation analyses are powerful tools for the identify potential diagnosis and treatment biomarkers in diseases such as cancer 1,2,[29][30][31] , bipolar disorder 2 , depression 32 , diabetes 33 , arteriosclerosis 34 , and others. For instance, Wan et al in 2020 applied bioinformatics analysis to identify eight candidate genes that could be a potential prognostic marker of thyroid carcinoma based on expression analysis profiles from the GEO database.…”
Section: Biomarker Identificationmentioning
confidence: 99%